Perioperative Severe Hypotension in a Patient with Multiple Endocrine Neoplasia Type IIb and Bilateral Adrenalectomies: Time to Review the Evidence for Stress Dose Steroids. (9th November 2016) - Tan, Jens; Zavala, Acsa; Hagan, Katherine B.; Van Meter, Antoinette; Williams, Uduak Ursula; Zhang, Wei; Owusu-Agyemang, Pascal
Abstract : Multiple endocrine neoplasia type IIb (MEN IIb) is an endocrine disorder which can manifest with tumors such as pheochromocytomas and neuromas. We present the case of a patient with MEN IIb, after bilateral adrenalectomies, on maintenance steroid replacement, who underwent a neuroma resection and developed severe hypotension. There is persistent controversy regarding the general administration of perioperative "stress dose" steroids for patients with adrenal insufficiency. While the most recent literature suggests that stress dose steroids are unnecessary for secondary adrenal insufficiency, the rarer form of primary adrenal insufficiency always requires supplemental steroids, specifically hydrocortisone, when undergoing surgical procedures.